Formulating the Regional Regulation Draft of Pangandaran Regency on Optimizing Labor Protection Through Employment Social Security - Achmad Sodik Sudrajat; Hafid Aditya Pradesa; Nur Imam Taufik (TGO Journal of Community Development, 2025)
This community service and academic policy drafting initiative addresses the critical economic vulnerability of workers in Pangandaran Regency, West Java, where the local labor force is predominantly concentrated in the informal sector, exceeding 96 percent of the total working population. Despite robust national mandates such as Presidential Instruction Number 2 of 2021, local workforce participation in mandatory employment social security remains inadequate, driven by structural constraints, limited financial literacy, and administrative barriers. Utilizing a normative-empirical legal research methodology combined with participatory action research, this project facilitated the systematic formulation of a comprehensive Regional Regulation Draft (Raperda) aimed at optimizing labor protection through BPJS Ketenagakerjaan. The academic and policy intervention successfully established rigorous philosophical, sociological, and juridical frameworks, defining actionable implementation strategies such as aggregator-based community outreach, decentralized socialization, and strict administrative compliance mechanisms linked with public licensing services. Moreover, the initiative incorporates digital transformation paradigms and public sector risk management principles to ensure transparent, accountable, and sustainable administrative delivery. Ultimately, this regulatory framework bridges the persistent social protection gap, mitigates extreme poverty, safeguards vulnerable formal and informal laborers against socioeconomic shocks, and serves as a replicable model for inclusive regional governance across Indonesia.